Driving Factors Of Economic Development In East Java: Government Expenditure, Per Capita Income, And Infrastructure Investment - Anitasari, Hening; Fauzi Aziz, Khalid; Budi Setiawan, Muhammad (INQUISITIVE : International Journal of Economic, 2024)
This study aims to elucidate the impact of government spending, per capita income, and infrastructure investment on economic development in East Java Province. The research employs a descriptive quantitative approach, utilizing secondary data in the form of cross-sectional data obtained from the Central Statistics Agency (BPS) website. The sample encompasses all districts in East Java. Data analysis is conducted using multiple linear regression methods for testing purposes. The individual findings indicate that government spending does not significantly affect economic development; per capita income has a positive and significant influence on economic development; and infrastructure investment is statistically insignificant. The implications of these three points suggest that the government should adopt a more strategic and efficient approach to national financial management